O percurso de mudança do item onde na perspectiva da gramaticalização - Fernanda Cunha Pinheiro da Silva (2008)
This work presents an analysis of the word onde under the perspective of the grammaticalization. It was made a diachronic quantitative study in written texts of the archaic, modern and contemporary Portuguese, and in the speech of the Minas Gerais' dialect. We confirm that the word evolves from a lexical function - as place adverb -, to a grammatical function - as relative pronoun - and, although in a very little productive way, a still more grammatical function - as intersentencial conjunction. The fact of the process of grammaticalization of onde does not show the typical trajectory of this phenomenon (cf. Vitral, (2006)), made us consider the distribution and the role of the word aonde and others expressions competing with onde. We conclude that the linguistic variation phenomenon affects the presumed evolution of a word in grammaticalization process.